Prognostic significance of Glutamine-Related Solute Carriers in luminal breast cancer - Erkan, Busra (2025)
Background Breast cancer (BC) is a heterogeneous disease comprising diverse molecular and cellular subtypes. Oestrogen receptor-positive (ER+) BC accounts for approximately 75% of all BC cases. Although ER+ BC generally responds well to endocrine therapy, approximately 15% of tumours show intrinsic resistance, while an additional 30–40% develop resistance over time, leading to relapse, metastasis, and poor patient outcomes. Proliferating cancer cells heavily depend on glutamine for survival and growth. Glutamine is transported across the plasma membrane via Solute Carrier (SLC) proteins, where it serves as a key metabolic substrate to support energy production and biosynthesis of essential cellular components. This study aimed to provide a holistic view of SLCs expression in BC using multiple datasets. Among these SLCs, SLC1A5, SLC7A5, and SLC3A2 were associated with poor prognosis, particularly in highly proliferative ER+ BC/Lum B BC. Despite growing evidence highlighting the importance of these SLCs in metabolic regulation, their specific role in ER+ BC tumour progression remains unclear. Additionally, the individual and combined inhibition of these poor prognosis-associated SLCs was evaluated through functional assays to determine their impact on tumour progression in Lum BC cell lines. Furthermore, the study explored the therapeutic potential of novel genes associated with these SLCs, providing insights into their role in disease progression and potential as therapeutic targets.